Densified alumina obtained by two-step sintering: Impact of the microstructure on mechanical properties. Issue 8 (1st June 2020) - Lóh, N.J.; Simão, L.; Jiusti, J.; Arcaro, S.; Raupp-Pereira, F.; De Noni, A.; Montedo, O.R.K.
Abstract: The impact of the microstructural properties of alumina on its mechanical properties is examined in this study. Furthermore, a comparison of the mechanical behaviours of alumina samples obtained by two-step and existing sintering techniques is presented. The results are rationalised by evaluating the changes in the densities and grain sizes of alumina samples. Different two-step treatments were used on commercial alumina (99.7 mass%-Al2 O3 content, 0.73 μm average particle size) and compared with the existing sintering technique. Alumina powder was formed by uniaxial pressing, and the samples were treated using heat. Microstructural analyses of the samples were performed with a scanning electron microscope. The mean grain size was determined via the intercept method. Porosity was determined by the relationship between the apparent and theoretical densities of the sintered alumina. The bending strength test was performed based on ASTM 1161–13. Fracture toughness was measured based on the notch method. The microhardness test was performed using the Knoop technique. The results showed that mechanical properties of the samples prepared using two-step sintering were improved—the bending strength, fracture toughness, and Knoop microhardness increased from 286 to 303 MPa, 4.09–4.35 MPa m 0.5, and 17.5–17.6 GPa, respectively—compared with those fabricated using the existing sintering technique, even with a higher porosity of 2.36% in samples obtained by two-step sintering and 1.80% in the existing sintering technique. Factorial analysis demonstrated that the temperature and holding time of the second step individually affect the relative density; however, the impact of temperature is more significant. Despite this, the interaction between temperature and holding time of the second step has the most significant impact on the average grain size.